Comparative literature : theory and practice - Das, Sisir Kumar; Deba, Amiẏa (Indian Institute of Advanced Study in association with Allied Publishers, New Delhi, 1989)
Papers presented at a seminar held at Indian Institute of Advanced Studies, Shimla on 22-26 June 1987.